2022
DOI: 10.1111/risa.13878
|View full text |Cite
|
Sign up to set email alerts
|

Are some narratives better than others?: The impact of different narrative forms on adolescents’ intentions to text and drive

Abstract: Psychological reactance theory posits individuals seek to restore freedom when threatened. Communication scholars have hypothesized persuasive messages can constitute threats to freedom. The current study engages questions about the potential for different forms of narratives in public service announcements (PSAs) to trigger freedom threats by examining responses to a PSA campaign that utilized three forms of narrative (celebrity testimonials, peer testimonials, and accident stories) to decrease adolescent tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In our study, the positive and ambivalent scenarios, however, suggested that there is a cure and they probably lower the fear of the disease; with regard to the ambivalent scenario, we can hypothesize the stimulation of anger or resignation as the last emotion the person came into contact with, when the information passed on stated that the cure existed but was not available due to economic reasons. The recent study by Scherr et al ( 45 ) showed that anger solicitation in the use of persuasive scenarios lowers the intention to follow the desired directions of the preventive campaign.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the positive and ambivalent scenarios, however, suggested that there is a cure and they probably lower the fear of the disease; with regard to the ambivalent scenario, we can hypothesize the stimulation of anger or resignation as the last emotion the person came into contact with, when the information passed on stated that the cure existed but was not available due to economic reasons. The recent study by Scherr et al ( 45 ) showed that anger solicitation in the use of persuasive scenarios lowers the intention to follow the desired directions of the preventive campaign.…”
Section: Discussionmentioning
confidence: 99%